Ocular complications of head injury in children (1991)
Ocular complications occurred in 28%, of children with head injury. Neuro-ophthalmological lesions made up one-third or these complications, mostly involved the optic nerve, and were associated with other focal neurological signs more frequently than non-neural ocular complications. Lesions or the posterior visual pathways were rare but tended to be permanent.